Organization of treatment and health resort rehabilitation of elderly and long-living patients with cardiovascular diseases in hospital for war veterans - A. K. Kashirin; M. A. Kachkovsky; S. N. Brylyakova; V. P. Artischev; I. D. Berezhnov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The Russian Federation belongs to the countries with very high cardiovascular risk. Data on risk factors for death in people of old age and long-livers are not well understood. Objective. To summarize the experience of organizing treatment and inpatient rehabilitation of elderly patients and long-livers with cardiovascular diseases, to assess their cardiovascular risk factors. Methods. The study involved 50 patients, aged from 77 to 97 years (average age – 86.6 ± 4.9 years), who underwent treatment and rehabilitation for cardiovascular diseases. 32 (64 %) people corresponded to old age, and 18 (36 %) people over the age of 90 years were long-livers. There were 36 (72 %) women and 14 (28 %) men. Results. All 50 patients had arterial hypertension. Angina pectoris was diagnosed in 49 (98 %) patients. One myocardial infarction was suffered by 4 (8 %) people, two – 3 (6 %). 7 (14 %) people had a stroke, and another (2 %) suffered from the disease twice. Atrial fibrillation was diagnosed in 8 (16 %) patients, diabetes mellitus – in 11 (22 %). Сarotid arteries stenoses were found in 23 (95.8 %) patients, in 5 of them up to 50–55 %, including one occlusion. All patients were discharged with improvement after complex therapy in accordance with guidelines. Conclusions. A system for the rehabilitation of elderly patients and long-livers with cardiovascular diseases has been developed. Patients of older age groups have very high cardiovascular risk and prevalence of cardiovascular risk factors. Relatively small increases in blood pressure, the degree of arterial stenosis of a less hemodynamically significant level, and the use of combined therapy for cardiovascular diseases are factors that make it possible to survive until the age of long-livers.